Anaemia in Indians aged 10–19 years: Prevalence, burden and associated factors at national and regional levels. Issue 4 (20th June 2022) - Scott, Samuel; Lahiri, Anwesha; Sethi, Vani; de Wagt, Arjan; Menon, Purnima; Yadav, Kapil; Varghese, Mini; Joe, William; Vir, Sheila C.; Nguyen, Phuong Hong
Abstract: Anaemia control programmes in India are hampered by a lack of representative evidence on anaemia prevalence, burden and associated factors for adolescents. The aim of this study was to: (1) describe the national and subnational prevalence, severity and burden of anaemia among Indian adolescents; (2) examine factors associated with anaemia at national and regional levels. Data ( n  = 14, 673 individuals aged 10–19 years) were from India's Comprehensive National Nutrition Survey (CNNS, 2016–2018). CNNS used a multistage, stratified, probability proportion to size cluster sampling design. Prevalence was estimated using globally comparable age‐ and sex‐specific cutoffs, using survey weights for biomarker sample collection. Burden analysis used prevalence estimates and projected population from 2011 Census data. Multivariable logistic regression models were used to analyse factors (diet, micronutrient deficiencies, haemoglobinopathies, sociodemographic factors, environment) associated with anaemia. Anaemia was present in 40% of girls and 18% of boys, equivalent to 72 million adolescents in 2018, and varied by region (girls 29%–46%; boys 11%–28%) and state (girls 7%–62%; boys 4%–32%). Iron deficiency (ferritin < 15 μg/L) was the strongest predictor of anaemia (odds ratio [OR]: 4.68, 95% confidence interval [CI]: [3.21, 6.83]), followed by haemoglobinopathies (HbA2 > 3.5% or any HbS) (OR: 2.81, 95% CI: [1.66, 4.74]), vitamin A deficiency (serum retinol <20 ng/ml) (OR: 1.86, 95% CI: [1.23, 2.80]) and zinc deficiency (serum zinc < 70 μg/L) (OR: 1.32, 95% CI: [1.02, 1.72]). Regional models show heterogeneity in the strength of association between factors and anaemia by region. Adolescent anaemia control programmes in India should continue to address iron deficiency, strengthen strategies to identify haemoglobinopathies and other micronutrient deficiencies, and further explore geographic variation in associated factors. Abstract : Conceptual framework for factors associated with anaemia in adolescents. Boxes with a solid outline are factors included in the regression analysis and boxes with a grey dotted outline are factors not included. Data on food security were collected in the Comprehensive National Nutrition Survey, but were not publicly available at the time of writing. Key messages: The Comprehensive National Nutrition Survey (CNNS) 2016–2018 is the only nationally representative survey to measure haemoglobin, haemoglobinopathies, biomarkers of micronutrient deficiencies, diet and social factors in Indian adolescents aged 10–19 years. Using CNNS data, we found that 28.5% of adolescents (girls: 39.6%, boys: 17.6%) were anaemic, with variation by region or state. Our prevalence estimates translate to 72 million adolescents being anaemic, with Uttar Pradesh having twice as many anaemic adolescents as any other state. Iron deficiency, haemoglobinopathies, vitamin A deficiency and zinc deficiency were associated with an increased risk of anaemia; these associations may vary subnationally.